The Burden of Thalassemia Major in Punjab, Pakistan: A Cross-Sectional Analysis from Sargodha with Focus on Gynecology Parameters - Muhammad Hassam Rehm, Abdul Rauf, Irsa Zulfiqar, Asma Ali, Aftab Nazir, Qamar Zehra, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: This study aimed to assess the burden of thalassemia major in Punjab, Pakistan, with a particular focus on gynecological complications among female patients. The study evaluated disease prevalence, associated complications, and healthcare challenges in the region. Study Duration: January 2022 to March 2023. Study Place: Niazi Medical College and District Headquarter (DHQ) Hospital, Sahiwal, Punjab, Pakistan. Study Type: Cross-sectional observational study with retrospective chart review and structured patient interviews. Methodology: A sample of 162 thalassemia major patients was enrolled. Data were collected through structured questionnaires, medical records, and laboratory reports. Variables analyzed included demographic characteristics, clinical symptoms, transfusion frequency, iron overload complications, and gynecological parameters for females aged 12 and above. Quantitative data were assessed using SPSS v26 with descriptive statistics and chi-square tests. Results: Key findings included high prevalence rates, frequent transfusion dependence, and significant gynecological complications such as delayed puberty (32%) and menstrual irregularities (28%). Eight tables were included, with detailed analysis of demographic, clinical, and gynecological parameters. Discussion: The study highlights the substantial burden of thalassemia major in Punjab, with notable reproductive health challenges. Socioeconomic factors, lack of awareness, and inadequate healthcare infrastructure exacerbate disease management difficulties. Conclusion: Thalassemia major imposes a heavy burden on patients and healthcare systems in Punjab, necessitating improved screening, genetic counseling, and specialized gynecological care for female patients. Keywords: Thalassemia major, Punjab, Pakistan, gynecology, transfusion-dependent anemia, reproductive health.